Implementasi Penyelenggaraan Pariwisata dalam Peningkatan Pendapatan Asli Daerah (Studi Kasus Kawasan Sawarna Kabupaten Lebak) - Humaedi, Imad; Budiati, Ayuning; Yulianti, Rina (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research aims to find out the success of the implementation of tourism in increasing local revenue, to find out the factors that hinder the implementation of tourism in increasing local revenue, and to find out the efforts that can be made to improve the implementation of tourism in increasing local revenue. This research was conducted on in-depth disclosure, so the qualitative approach was used to analyze the research data; it was related to the phenomenon of the problems studied and researched. Based on the discussion of the results of interviews with informants, it can be concluded that several aspects developed by Van Meter and Van Horn in analyzing research on the Implementation of Tourism Implementation in Increasing Regional Original Revenue (Case Study of Sawarna Area, Lebak Regency) can be seen that the Implementation of Tourism Implementation policies in Increasing Regional Original Revenue in Lebak Regency is not optimal, in its implementation it has not shown satisfactory results so that the purpose of organizing tourism in increasing local revenue cannot be adequately achieved.